Pharmacokinetics and pharmacodynamics of granulocyte-macrophage colony-stimulating factor and zidovudine in patients with AIDS and severe AIDS-related complex. - Hewitt, R G (1993)
Granulocytopenia is a complication of human immunodeficiency virus disease, as well as a toxic manifestation of zidovudine therapy. To evaluate pharmacokinetic and pharmacodynamic relationships, 11 AIDS-AIDS-related complex patients who had developed zidovudine-associated granulocytopenia (mean absolute neutrophil count, 1,077/mm3) were examined after addition of granulocyte-macrophage colony-stimulating factor (GM-CSF) to zidovudine. GM-CSF was administered as a daily (1.0 or 0.3 micrograms/kg) or every-other-day (0.3 micrograms/kg) subcutaneous dose over a 28-day period. Zidovudine was continued at the same daily dosage as was previously being administered. Of 11 patients, 7 (1.0 micrograms/kg, n = 5; 0.3 micrograms/kg, n = 2) had a pharmacologic response to GM-CSF with an increase to a mean absolute neutrophil count of 3,189 cells per mm3 at 4 weeks (P < 0.05). The peak concentration of GM-CSF in plasma ranged from 11.5 to 84.4 pg/ml, and the time to peak ranged from 1 to 3 h. No correlation between GM-CSF disposition and hematologic response was noted. A decreased plasma zidovudine-glucuronide/zidovudine ratio was noted after 1 week of GM-CSF, and an increase in the area under the plasma concentration-versus-time curve for zidovudine was found in three patients after 4 weeks. Low doses of GM-CSF can raise the granulocyte count in patients with zidovudine-induced neutropenia. The use of GM-CSF and zidovudine may represent a viable treatment option for persons with human immunodeficiency virus infection who develop neutropenia while receiving zidovudine but do not tolerate alternative nucleoside analogs. Further studies are needed to assess the complex interaction between these two agents.